Beyond Project Management Technicalities: Uplifting the Role of Leadership Towards Project Success (Tanzania Journal for Population studies and Development, 2023)
This article highlights and discusses the critical role of leadership for effectively managing and achieving project results. As opposed to the conventional and once dominating thinking of project management which linked project success to project technicalities, this article considers project leadership a central issue for project success or failure. The article stipulates that, despite the strategic importance of robust project management techniques in effectively controlling and executing activities, at the absence of proper project leadership skills approaches may render a project to leadership related failures. To appreciate the role of leadership towards project success, this article highlights and discusses different elements of project leadership and management—including blueprint and adaptive approaches, similarities and differences between management and leadership—and how they interact towards effective project management; leadership theories, styles and skills required for effective project leadership and management. The article concludes that generally project leadership is a critical factor towards project success without undermining the importance of conventional project management methodologies, tools and software. Such understanding demonstrates clearly that, to be successful, project managers are obliged to employ holistic and integrative methodologies and approaches necessary for making their projects more relevant and sustainable; taking into account that there is no one single project management and leadership approach or style that is superior to the rest. Last but not least, as it is the case with management aspect, project leadership needs to be a continuous process to be employed at different stages of the project cycle management.